2007
DOI: 10.1071/wf06094
|View full text |Cite
|
Sign up to set email alerts
|

Resprouting responses of Acacia shrubs in the Western Desert of Australia - fire severity, interval and season influence survival

Abstract: The hummock grasslands of arid Australia are fire-prone ecosystems in which the perennial woody plants mostly resprout after fire. The resprouting ability among these species is poorly understood in relation to environmental variation; consequently, little is known about the impacts that contemporary fire regimes are having on vegetation within these systems. We examined the resprouting ability of adults and juveniles of four widespread Acacia species (A. aneura, A. kempeana, A. maitlandii, A. melleodora) by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 37 publications
3
40
0
2
Order By: Relevance
“…Repeated sampling of surviving A. aneura individuals in 2004 and then in 2009, confirmed that fire return intervals of less than 10 years are incompatible with the growth and development requirements of A. aneura: all individuals were still reproductively immature and none had developed a canopy that could potentially shade-out grasses. While our fire survival results need to be interpreted with caution (due to the lack of survival data just prior to the event), they do align with our current understanding of the fire response of the three Acacia species (Hodgkinson and Griffin 1982;Wright and Clarke 2007), and therefore further highlight the comparatively high risk of fire death in A. aneura. Thus, we were able to demonstrate that in both the dune (grassland) and swale (shrubland) habitats, post-fire persistence in this non-sprouter will depend on whether or not enough time passes between fire events for it to establish a seed bank.…”
Section: Do Biotic Interactions Influence Patch and Boundary Dynamics?supporting
confidence: 79%
See 1 more Smart Citation
“…Repeated sampling of surviving A. aneura individuals in 2004 and then in 2009, confirmed that fire return intervals of less than 10 years are incompatible with the growth and development requirements of A. aneura: all individuals were still reproductively immature and none had developed a canopy that could potentially shade-out grasses. While our fire survival results need to be interpreted with caution (due to the lack of survival data just prior to the event), they do align with our current understanding of the fire response of the three Acacia species (Hodgkinson and Griffin 1982;Wright and Clarke 2007), and therefore further highlight the comparatively high risk of fire death in A. aneura. Thus, we were able to demonstrate that in both the dune (grassland) and swale (shrubland) habitats, post-fire persistence in this non-sprouter will depend on whether or not enough time passes between fire events for it to establish a seed bank.…”
Section: Do Biotic Interactions Influence Patch and Boundary Dynamics?supporting
confidence: 79%
“…Both of the shrubs usually have prolific post-fire seedling recruitment but they differ in terms of their ability to resprout. Existing data show that adult A. murrayana has a fire resprouting probability of between 0.63 and 0.75 (Hodgkinson and Griffin 1982) whereas that of A. melleodora is comparatively low (0.26-0.38) and varies with fire season and intensity (Wright and Clarke 2007). T. basedowii is often killed by fire and has fire-cued seed germination.…”
Section: Study Site and Target Speciesmentioning
confidence: 97%
“…One possibility is incomplete protection from heat in newly developing buds which may be located close to the soil surface, and with only a thin bark layer which gradually thickens over time. Wright and Clarke (2007) found that central Australian arid hummock grasslands Acacia species with more deeply buried buds were more resilient to high-severity soil heating than those with shallow buds, and this has been reported also for species elsewhere (Canadell et al 1991;Moreno and Oechel 1991).…”
Section: Discussionmentioning
confidence: 79%
“…Our results, however, were not expected because all of the species are top killed and resprouted from basal rather than epicormic buds after crown fire. Instead, basal buds are thought to be protected from the heat of the fire by soil and not thicker bark (Wright and Clarke 2007). There are two possible explanations for these results; firstly, non-sprouters may preferentially allocate resources to reproduction rather than bark.…”
Section: Resprouting Vigourmentioning
confidence: 89%